Global Trends and HRM - Bertalan, Péter; Boldizsár, Bettina (Acta Scientiarum Socialium, 2015)
Global Trends and HRM. From the point of view of the social sciences the beginning of the 21st century brought great changes which were partly pleasant and partly unpleasant. Globalization is an economic phenomenon, which involves the integration of national economic systems, through the growth of multinational and transnational corporations, through the capital flows, and through international trade and investment. Globalization entails social, political, technological, environmental and cultural cross-border exchange and links, which connect individuals, communities, businesses and governments, all over the world. The paper investigates the present situation and trends of Human Resources Management in the globalized world.